Green development performance of water resources and its economic-related determinants - Li, Wei (2019)
In the context of severe water shortage and pollution, enhancing the green total-factor productivity of water resources (GTFPWR) is critical for the green development of water resources. This study aims to propose a novel two-stage analytical framework, in which the GTFPWR is measured in the first stage and its economic-related determinants are examined in the second stage. In this two-stage analytical framework, we improve and integrate four classical methods, namely, the undesirable-super-slack-based measure, global Malmquist-Luenberger productivity index, system generalized method of moments and fixed-effects panel threshold models. The proposed analytical framework is capable of addressing four practical issues simultaneously: equal efficiency, undesirable outputs, impact scenarios and endogenous biases. We can thus more accurately and comprehensively evaluate the GTFPWR and its determinants. To validate the applicability and suitability of the proposed methodology, we collected the panel data about water resources across 30 provinces in China from 2005 to 2015 for an empirical study. The main findings of this study are as follows: i) the level of water utilization is a critical factor for the government to decide whether to increase the GTFPWR via foreign direct investment and trade; ii) the amount of wastewater should be effectively reduced to mitigate the conflicts between urbanization and the GTFPWR growth; iii) inland provinces, particularly Shanxi, Hainan and Yunnan, need to improve water technologies and management to increase their low-GTFPWR-growth rates. Our analytical framework is practical to evaluate water-use productivity and its determinants, while our empirical findings provide new insights into the green development of water resources and may shed light on future policies of environmental management.